The power of controversy: the role of conflict on consumers- willingness to pay - Sá, Diogo Miguel Pereira (2022)
This study aims to understand the reasons behind some brands do not reap all the benefits from engaging in controversial topics. I hypothesized that controversial brands are perceived as more conflictual than non-controversial brands and that that conflict influenced the consumers’ willingness to pay. To test the hypothesis an experimental study was conducted in which the scenarios presented were chosen based on a pre-test experiment. Results supported both hypotheses.